-8=3(-x+2)-x

Simple and best practice solution for -8=3(-x+2)-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8=3(-x+2)-x equation:


Simplifying
-8 = 3(-1x + 2) + -1x

Reorder the terms:
-8 = 3(2 + -1x) + -1x
-8 = (2 * 3 + -1x * 3) + -1x
-8 = (6 + -3x) + -1x

Combine like terms: -3x + -1x = -4x
-8 = 6 + -4x

Solving
-8 = 6 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-8 + 4x = 6 + -4x + 4x

Combine like terms: -4x + 4x = 0
-8 + 4x = 6 + 0
-8 + 4x = 6

Add '8' to each side of the equation.
-8 + 8 + 4x = 6 + 8

Combine like terms: -8 + 8 = 0
0 + 4x = 6 + 8
4x = 6 + 8

Combine like terms: 6 + 8 = 14
4x = 14

Divide each side by '4'.
x = 3.5

Simplifying
x = 3.5

See similar equations:

| 16+5a=13a | | 1-2r=8-3r | | 48(x^3)+27x(y^2)+16(x^2)y-9(y^3)=0 | | x^2+0.4x-0.3=0 | | 12n-(14m-8m)= | | 3-2y=15+14y | | 8n-(n+3)=9 | | 48(x^3)+27x(y^2)+16(x^2)y-9(y^2)=0 | | 5x-5+7x=17 | | 3x+2(x-6)=3 | | 96=600(.04)t | | -3x+=-54 | | 8+p=2p+3 | | X=log-25 | | 0.4x+0.7(x-3)= | | 66-5x=4x+18 | | -4x-4y=28 | | 2n^2-9n-18=0 | | -4m+=-15 | | 2x+4=(6-x) | | 11-7x=86-28x | | 6(y+5)=30 | | 3v(-8y^15n^3)=0 | | 5y-5+y+17=8y+20-6y | | 3(x-5)=-30 | | 2x+5y=6 | | A=1.2bh | | 4x+11=45-10x | | 7-2(5)=x | | -65.25=7.25n | | -18=6x+6(1+3x) | | 5+-11= |

Equations solver categories